RELATIONS BETWEEN CENTRAL AND LOCAL GOVERNMENT - Arben Ristemi (Journal of Bio-Based Marketing)
Municipalities in the Republic of North Macedonia enjoy increased autonomy as a result of the ongoing process of local government reform. This process leads to an increase in municipal activities in the areas of independent, expanded, and delegated competencies. In the area of ​​​​their competencies, the municipalities have full and exclusive authority to execute and issue by-laws that regulate them within the boundaries of the municipality and the standards defined by the primary legislation. Certain municipalities may be granted additional autonomy in certain areas, known as extended powers. Delegated powers are the primary duties of the central level that municipalities perform on their behalf. One of the activities of the municipalities is the approval of municipal acts, which must follow the applicable legislation. The applicable legislation in the Republic of North Macedonia provides for a system of administrative supervision of municipal activities. The key link between the municipalities and the responsible ministries, as supervisory authorities, is the Ministry of Local Self-Government (MLS), through which the channeling of the acts under consideration should function.